Can alkali metal doped zeolites be metallic? - Microwave conductivity of rubidium doped zeolite rho - Edmondson, M; Barker, P; Porch, A; Anderson, P; Edwards, P (2003)
Large crystallites of high purity zeolite rho have been synthesized by controlled monitoring of the aging and heating period of the mother gel. The microwave conductivity of Rb-rho samples doped with up to 20 Rb atoms p.u.c. was measured over the temperature range 15-300 K. Confirmation that the conductivity was due to rubidium doped zeolite rho and not decomposition products or residual rubidium metal was provided by XRD, TEM, and microwave loss measurements on zeolite supported silver particles, the latter providing the first experimental confirmation of the validity of the quasistatic analysis for highly conducting particles. At low concentrations of rubidium dopant the observed microwave responses were dominated by dielectric effects. In the sample Rb17/Rb-rho, a strongly temperature-dependent electronic contribution to the conductivity was observed above ∼150 K. In Rb 20/Rb-rho, conductivities in the range 1.5-2.3 S m-1 were observed between 15 and 300 K. The residual conductivity at 15 K indicates that the sample is indeed metallic, but the values of conductivity measured are low in comparison to conventional metals.